2020
DOI: 10.2166/wst.2020.241
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of composite sorbent for the treatment of aqueous solutions contaminated with methylene blue dye

Abstract: Abstract To apply the principles of sustainability, this study aims to prepare the composite sorbent from mixing of solid wastes that resulted from activities of treatment plants for wastewater and water supply. The manufacturing process depends on the mixing of sewage sludge with waterworks sludge at different proportions and the best mixture is modified by ferric nitrate solution. The prepared composite sorbent was evaluated as permeable reactive barrier (PRB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It also justifies why adsorbed chemical species on unoccupied sites do not interact. The Langmuir model is used to determine the greatest sorption capacity (qmax, mg/g) of sorbent [89]. ))…”
Section: Sorption Process Modellingmentioning
confidence: 99%
“…It also justifies why adsorbed chemical species on unoccupied sites do not interact. The Langmuir model is used to determine the greatest sorption capacity (qmax, mg/g) of sorbent [89]. ))…”
Section: Sorption Process Modellingmentioning
confidence: 99%
“…The results indicated that the most effective conguration to safeguard a particular location is to surround it on three sides opposing the ow direction compared to a continuous barrier. 22 The use of commercial sorbents, 9,[23][24][25][26] industrial wastes resulted as byproducts from various industries, [27][28][29] or manufacturing new valuable sorbents from these wastes [30][31][32] for elimination of chemicals from contaminated water is a crucial eld that has studied recently. This study aims to utilize clay, an abundant and cost-effective material in the Iraqi environment, as an LPB to control the migration of lead and nickel ions through groundwater and protect water resources.…”
Section: Introductionmentioning
confidence: 99%
“…The high cost of AC and the difficulties of its regeneration may be represented the main causes for limiting the utilization of this sorbent. Thus, new direction in the scientific researches was developed for finding the effective low-cost reactive materials to be the alternatives for activated carbon like dead macro fungi, walnut shells, olives pips, fruit barks, wastes of coconut, activated sludge and other bio-materials (Al Juboury et al, 2020;Özacar and S ¸engil, 2005).…”
Section: Introductionmentioning
confidence: 99%